2018
DOI: 10.1111/dom.13375
|View full text |Cite
|
Sign up to set email alerts
|

The management of type 2 diabetes with fixed‐ratio combination insulin degludec/liraglutide (IDegLira) versus basal‐bolus therapy (insulin glargine U100 plus insulin aspart): A short‐term cost‐effectiveness analysis in the UK setting

Abstract: AimTo evaluate the cost‐effectiveness of IDegLira versus basal‐bolus therapy (BBT) with insulin glargine U100 plus up to 4 times daily insulin aspart for the management of type 2 diabetes in the UK.MethodsA Microsoft Excel model was used to evaluate the cost‐utility of IDegLira versus BBT over a 1‐year time horizon. Clinical input data were taken from the treat‐to‐target DUAL VII trial, conducted in patients unable to achieve adequate glycaemic control (HbA1c <7.0%) with basal insulin, with IDegLira associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Similar long-term analyses have been conducted in the UK, the Netherlands, Sweden and Slovakia, all of which showed IDegLira to be cost-effective versus basal-bolus insulin and/or basal insulin plus GLP-1 receptor agonists from the perspective of the respective healthcare payer [ 44 47 ]. For the UK, a recent short-term CEA also showed that IDegLira was likely to be cost-effective even over 1 year relative to treatment with basal-bolus insulin therapy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar long-term analyses have been conducted in the UK, the Netherlands, Sweden and Slovakia, all of which showed IDegLira to be cost-effective versus basal-bolus insulin and/or basal insulin plus GLP-1 receptor agonists from the perspective of the respective healthcare payer [ 44 47 ]. For the UK, a recent short-term CEA also showed that IDegLira was likely to be cost-effective even over 1 year relative to treatment with basal-bolus insulin therapy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…This number is expected to exceed 700 million by 2045 (International Diabetes Federation, 2019), with type 2 diabetes accounting for a large proportion of these patients (Simpson & King, 2015). Type 2 diabetes is a metabolic disease that involves gradual impairment of glucose regulation because of islet β‐cell dysfunction and insulin resistance (Drummond, Malkin, Du Preez, Lee, & Hunt, 2018; Greig & Scott, 2015; Nauck, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies had a similar bias profile, except double counting and reporting/dissemination had unclear information. Four 35 51 52 57 and 14 studies 21 24 28 30 35 36 49 51 52 54 57 61 66 69 had bias related to model structures and data, respectively. All studies were unclear for internal consistency bias.…”
Section: Resultsmentioning
confidence: 99%